Analisis Kestabilan Lubang Bukaan Dengan Menggunakan Data Dari Alat Ukur Flat Jack Pada Dinding Tambang Bawah Tanah PT. Nusa Alam Lestari, Sawahlunto - Muhammad Nazri; Muhammad Giatman (Journals Mining Engineering : Bina Tambang, 2018)
Abstract. The geomechanical aspect is one of the important aspects that must be considered to maintain the stability of the opening hole. Other aspects that must be considered are geology, hydrogeology and technical regarding buffer. Geomechanics monitoring in underground mines includes: insitu stress measurement, rock deformation monitoring, and rock mass weighting. There are many insitu stress measurements including: overcoring techniques, hydraulic fracturing techniques, and Flat Jack methods.There are several thing to do, such as determining the testing point, making a hole for the Flat position (test point), and checking the deformation that occurs at the test point. Then get the rock stress value using the calculation of gravity. Before calculating gravitational stress it is necessary to take some data. Next to get the value of rock compressive strength, the sample was tested in the laboratory using a point load index.Based on the test of the flat jack, the calculation of gravity, and the results of testing the sample is not greater in value than the sample testing, which means that the condition is able to withstand the voltage acting on the study site.Kata kunci :Flat jack, Geotechnical, Rock stress, Gravitational force calculation, Underground mine